Analisis leading indicator sektor pertanian di Indonesia tahun 2004-2022: Leading indicator analysis of the agricultural sector in Indonesia in 2004-2022 - Ningsih, I Kadek Mira Merta; Astuti, Erni Tri (Analisis Kebijakan Pertanian, 2025)
The agricultural sector contributes significantly to national GDP, but its fluctuating trends and indications of policy inefficiencies require accurate predictive tools to formulate the right policies to maintain its stability. The purpose of this study is to provide an overview and to estimate the leading indicators of the agricultural sector relative to its real GDP, in both long-term and short-term relationships. This study used secondary data in the form of quarterly data sourced from Statistics Indonesia (BPS), Bank Indonesia (BI), the International Monetary Fund (IMF), and the Financial Services Authority (FSA) from 2004 to 2023. The study used Cross-Spectral Analysis. The results of the study show that there are five leading indicators: agricultural product exports, agricultural product imports, BI-Rate, exchange rate (rupiah/USD), and World Tea Price Index. Based on this result, forecasting was carried out using the Autoregressive Distributed Lag (ARDL) model, and the ARDL (7,3,1,6,7,7) was formed. In the long-term model, significant variables are agricultural product exports, agricultural product imports, and the exchange rate (rupiah/USD). Meanwhile, in the short-term model, the lags of real GDP in the agricultural sector, the BI-Rate, and the World Tea Price Index are significant. These forecasting results indicate that agricultural sector stabilization policies need to account for differences between short- and long-term dynamics. Therefore, strategies for stabilizing Indonesian agriculture are formulated by selecting short-term and long-term policies based on leading agricultural sector indicators.